(untitled) (UUM Journal of Legal Studies, 2021)
Many recent legislations and international principles tend to apply the pre-contractual duty of disclosure as one of the most substantial principles governing the pre-contracting phase, such as Article 1112-1 of the Amended French Civil Code of 2016, Article 1337 of the Amended Italian Civil Code and Article 13 of chapter 2 of the Common European Sales Law, etc. However, the Palestinian legislature has ignored enacting legal provisions imposing the pre-contractual duty of disclosure which causes legislative deficiencies in the legislative remedies of the subject of pre-contractual duty of disclosure. In this regard, this paper suggests orientations for the formulation of the provisions of the pre-contractual duty of disclosure in the Palestinian Civil Code Draft (PDCC). To do so, a comparative analytical approach with the French civil code is used to illustrate the Palestinian legislative deficiencies and the urgent need to legislate a legal article which obligates the negotiating party to disclose any substantial information for the satisfaction of the other party. As such, the contractual equilibrium entails that the pre-contractual duty of disclosure has its own independent essence from all the theories that the jurisprudence adopted as a legal basis for this duty.